Climate-Induced Displacement and the International Protection of Forced Migrants - Aleinikoff, T. Alexander (Social research, 2024)
In coming years, scores of millions of people will be forced from their homes because of the effects of the climate crisis and other environmental events. While there is general recognition that those displaced by climate events merit assistance and protection, the existing international refugee regime does not provide an adequate framework for action. This article proposes an approach that focuses on the fact of displacement due to the climate crisis and embraces a right not to be displaced. It thus centers questions of accountability and root causes and embeds claims to climate justice in discussions of regime reform. Climate displacement provides an opportunity—indeed, the necessity—for a fundamental rethinking of the prevailing protection paradigm.